2017
DOI: 10.17221/93/2015-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of bovine mammary peptide transporters in response to tripeptide and lactogenic hormone treatment

Abstract: Cui Y., Zhang X., Guo C., Du R., Ailun G., Ao C., Gao M. (2017): Identification and characterization of bovine mammary peptide transporters in response to tripeptide and lactogenic hormone treatment. Czech J. Anim. Sci., 62, 296-305.Oligopeptide transportation is mediated by the peptide transporter (PepT), which consists of two isoforms, PepT1 and PepT2. Because PepT play essential roles in amino acid metabolism and cell growth, the aim of the present study was to identify these transporters in bovine mammary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Later studies demonstrated that PEPT2 mRNA and protein are also expressed in lactating and cultured bovine mammary gland epithelial cells. Coupled with lactogenic hormones (prolactin, hydrocortisone, and insulin), gene expression of PEPT2 was significantly enhanced (Zhou et al, 2011;Cui et al, 2017). In the bovine mammary gland, reabsorption of peptides is very important for milk protein synthesis, in which PEPT2 is essential to maintain peptide homeostasis and to reduce drug contamination in milk, especially during lactation (Zhou et al, 2011).…”
Section: Candidate Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Later studies demonstrated that PEPT2 mRNA and protein are also expressed in lactating and cultured bovine mammary gland epithelial cells. Coupled with lactogenic hormones (prolactin, hydrocortisone, and insulin), gene expression of PEPT2 was significantly enhanced (Zhou et al, 2011;Cui et al, 2017). In the bovine mammary gland, reabsorption of peptides is very important for milk protein synthesis, in which PEPT2 is essential to maintain peptide homeostasis and to reduce drug contamination in milk, especially during lactation (Zhou et al, 2011).…”
Section: Candidate Genesmentioning
confidence: 99%
“…In the bovine mammary gland, reabsorption of peptides is very important for milk protein synthesis, in which PEPT2 is essential to maintain peptide homeostasis and to reduce drug contamination in milk, especially during lactation (Zhou et al, 2011). Thus, the PEPT2 gene might influence milk production in cattle (Yang et al, 2015;Cui et al, 2017).…”
Section: Candidate Genesmentioning
confidence: 99%
“…Dipeptide (Methionyl-Methionine) positively affects JAK2-STAT5 and mTOR signaling pathways in BMECs after being absorbed by PepT2, thereby promoting β-casein synthesis and cell proliferation [84]. Studies also showed that after stimulation of BMECs with tripeptides and lactogenic hormones, the abundance of PepT1 and PepT2 can be increased, thereby promoting milk fat synthesis [85,86]. In addition, it has been shown that OPH3-1, a fraction of the octopus protein hydrolysis product bioactive peptide, promotes mammary epithelial cell proliferation and casein synthesis in mice [87].…”
Section: Peptidesmentioning
confidence: 99%
“…Several studies showed that peptides appear to be more efficient than free amino acid in promoting milk protein synthesis (Chen et al, 2020;Zhou et al, 2015;Zhou et al, 2020). This may be related to the action of aminopeptidase N and peptide transporter (Cui et al, 2017;Liu, Wang, Wang, Li, & Cao, 2010;Wang, Zhao, Liu, & Liu, 2016). Figure S1 shows the separation of fraction OPH3-1 into six portions labeled F1-F6 with RP-HPLC for further peptidomic profiling.…”
Section: Purification Of the Oph3 Fractions That Stimulated β-Caseimentioning
confidence: 99%
“…Overall, the peptide‐bound amino acid including Met, Phe, or Thr is necessary for the synthesis of milk protein. It is likely that either the peptides could be hydrolyzed extracellularly with the subsequent uptake of the component amino acids, di‐ or tri‐peptides, or the peptides could be completely transported into mammary secretory cells by the peptide transporter (Cui et al., 2017; Shennan & Boyd, 2014; Wang, Sun, Zhao, Liu, & Liu, 2019).…”
Section: Introductionmentioning
confidence: 99%